2019
DOI: 10.3758/s13423-019-01684-9
|View full text |Cite
|
Sign up to set email alerts
|

Are the facial gender and facial age variants of the composite face illusion products of a common mechanism?

Abstract: When the upper half of one face ('target region') is spatially aligned with the lower half of another ('distractor region'), the two halves appear to fuse together perceptually, changing observers' subjective perception of the target region. This 'composite face illusion' is regarded as a key hallmark of holistic face processing. Importantly, distractor regions bias observers' subjective perception of target regions in systematic, predictable ways. For example, male and female distractor regions make target re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Evidence suggests that this approach can produce high-quality data comparable to that obtained from in-person testing [ 46 48 ]. To give recent examples from our own research, we have found that online testing has produced clear, replicable results in visual search [ 49 , 50 ] and attention cueing [ 51 , 52 ] experiments, and studies of visual illusions [ 53 , 54 ]. However, we acknowledge that this approach is associated with some well-known limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that this approach can produce high-quality data comparable to that obtained from in-person testing [ 46 48 ]. To give recent examples from our own research, we have found that online testing has produced clear, replicable results in visual search [ 49 , 50 ] and attention cueing [ 51 , 52 ] experiments, and studies of visual illusions [ 53 , 54 ]. However, we acknowledge that this approach is associated with some well-known limitations.…”
Section: Discussionmentioning
confidence: 99%
“…When faces are altered to include competing identity information, identification may also be severely impacted [ 30 , 31 ]. For example, when the top half of one face (target region) is aligned with the bottom half of another (distractor region), observers' perception of the target region is biased [ 32 ]. In sequential matching paradigms, this ‘composite face effect’ results in observers making errors when judging the target region, often reporting that the target regions are different when they are in fact the same [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…When viewed by typical observers, faces are thought to engage holistic processing whereby distal features are processed in parallel and integrated into a unified perceptual whole, for the purposes of accurate and efficient interpretation (Farah, Wilson, Drain, & Tanaka, 1998;Maurer, Le Grand, & Mondloch, 2002;McKone & Yovel, 2009;Piepers & Robbins, 2013;Richler, Wong, & Gauthier, 2011). Evidence for this view is provided by the composite face illusion (Gray et al, 2020;Hole, 1994;Young, Hellawell, & Hay, 1987). When the bottom half of one face is spatially aligned with the top half of another, the two halves appear to fuse together perceptually, altering observers' perception of the individual regions.…”
Section: Introductionmentioning
confidence: 99%